SAT-020 Fluoxetine Administration Influences Serotonin-Driven Bone Remodeling During Lactation and Pregnancy Outcome in Mice - Fricke, Hannah P (J Endocr Soc, 2020)
Selective serotonin reuptake inhibitors (SSRI) are the most commonly prescribed class of antidepressants during pregnancy and lactation. SSRI decrease bone mineral density (BMD) across all ages and sexes. Lactation is also characterized by increased bone resorption to mobilize calcium due to the demands of lactation and achieves this via a serotonin-induced hormonal cascade. This serotonin-mediated bone loss is normally restored after weaning but is persistent when an SSRI is administered during the peripartum period. We hypothesize that the long-term BMD loss associated with fluoxetine administration during lactation will be seen in two sequential lactations and will have a more dramatic effect on maternal bone loss after the second lactation at both weaning and 3 months post-weaning. Female C57BL/6 mice were randomized to receive the SSRI fluoxetine hydrochloride (20 mg/kg) or saline daily from the beginning of pregnancy (E0), determined by the presence of a vaginal mucous plug, through the end of lactation (D21). They were then given a 3-week rest period before undergoing a second lactation with the same study design. Each group is paired to an age-matched virgin cohort to provide a non-lactating control. This created the following treatments: saline dam (S), fluoxetine dam (F), saline virgin pair (SV), and fluoxetine virgin pair (FV). Dual-energy X-ray absorptiometry (DEXA) was used to measure BMD of all groups throughout the peripartum period. At the end of gestation (E17.5), BMD was decreased in both the F and FV groups, and the BMD of the FV group remained persistently lower than the SV group across all timepoints. Both the F and S groups exhibited a dramatic decrease in BMD between E17.5 and the beginning of lactation (D2), then a slight increase between mid-lactation (D10) and at weaning (D21). There was an overall interaction between treatment and time for all groups across the peripartum period (p<0.0001). During the first peripartum period, the F dams that were mated had significantly increased pregnancy loss (p=0.0041) and pup mortality post-parturition compared to S mice. Of the dams that were inseminated, determined by the presence of a mucus plug, 63% of successfully mated S dams (n=19) resulted in a full-term pregnancy. Of those S dams (n=12), 25% lost their entire litter at the beginning of lactation, and 75% maintained their litter until weaning. In the F dams that were successfully mated (n=37), only 35% resulted in a full-term pregnancy. We conclude that fluoxetine administration during the peripartum period decreases long-term maternal BMD and that fluoxetine exhibits a drug-specific effect on the dam resulting in a notably decreased incidence of a successful pregnancy.